2008
DOI: 10.1364/oe.16.013233
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-random single photon counting for time-resolved optical measurement

Abstract: We report a new time-resolved optical measurement method which combines single photon counting and the spread spectrum time-resolved optical measurement method. A laser diode modulated with pseudo-random bit sequences replaces the short pulse laser used in conventional time-resolved optical systems, while a single photon detector records the pulse sequence in response to the modulated excitation. Periodic cross-correlation is used to retrieve the impulse response. Feasibility of our approach is validated exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…A comparison between our PRSPC and the conventional TCSPC approach had been discussed in [8] and the simulation results had shown that the PRSPC system can rebuild the original waveform with high accuracy theoretically.…”
Section: System Performance Verificationmentioning
confidence: 99%
See 3 more Smart Citations
“…A comparison between our PRSPC and the conventional TCSPC approach had been discussed in [8] and the simulation results had shown that the PRSPC system can rebuild the original waveform with high accuracy theoretically.…”
Section: System Performance Verificationmentioning
confidence: 99%
“…While its accuracy may be marginally inferior to that of the conventional TCSPC technique, PRSPC has two main advantages over TCSPC (see [8] for a comparison).…”
Section: System Performance Verificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Time-Domain (TD) systems are commonly used to perform NIR spectroscopy, but this technique has some limitations, as the high cost of equipment, the acquisition length and the sensitivity to ambient light. A novel, spread spectrum approach was presented in [1] where continuous wave (CW) laser sources are modulated by a pseudo-random bit sequence (PRBS). This approach can overcome the latter limitations, adding the advantages of CW systems (low cost of components, lower sensitivity to ambient light and shorter acquisition time).…”
Section: Introductionmentioning
confidence: 99%